RESEARCH AND EDUCATION CENTER AS A “POINT OF GROWTH” OF INNOVATION DEVELOPMENT OF A TECHNICAL UNIVERSITY - Igor R. Pleve; Alexandr E. Khramov; Aleksey V. Ivanov; Marina V. Khramova; Olga I. Moskalenko (Высшее образование в России)
The article is devoted to the experience of establishing a Research and EducationCenter (REC) «Nonlinear Dynamics of Complex Systems» at Saratov State Technical University named after Yuri Gagarin. The basic objective of REC was conducting of innovative interdisciplinary studies based on the application of the methods and concepts of nonlinear dynamics and integrated technologies (nano-, bio-, information and cognitive) with the active participation of students, postgraduates and young scientists. An important feature of the REC’s activity is a systematic participation of the leading Russian and foreign scientists, which is expressed in scientific workshops conducted on the basis of Saratov State Technical University, lectures for the students of the Technical University, as well as a work as the supervisors of the scientific projects and grants supported by international programs, the Russian Federal Program «Human resources», Russian Foundation for Basic Research, Ministry of Education and Science.